Pain neuroscience education: Which pain neuroscience education metaphor worked best? - Adriaan Louw; Emilio J. Puentedura; Ina Diener; Kory J. Zimney; Terry Cox (AOSIS, 2019)
Background: The use of pain neuroscience education (PNE) has been shown to be effective in reducing pain, improving function and lowering fear and catastrophisation. Pain neuroscience education utilises various stories and metaphors to help patients reconceptualise their pain experience. To date no individualised study has looked at which stories and metaphors may be the most effective in achieving the positive outcomes found with the use of PNE. Objectives: This study examined patient responses to the usefulness of the various stories and metaphors used during PNE for patients who underwent surgery for lumbar radiculopathy. Method: Twenty-seven participants who received preoperative PNE from a previous randomised control trial (RCT) were surveyed 1-year post-education utilising a 5-point Likert scale (0 - 'do not remember', 4 - 'very helpful') on the usefulness of the various stories and metaphors used during the PNE session. Participant demographics and outcomes data (pain intensity, function and pain knowledge) were utilised from the previous RCT for analysis and correlations. Results: Nineteen surveys were returned for a response rate of 70%. No story or metaphor mean was below 2 - 'neutral', lowest mean at 2.53; 6 of the 11 stories or metaphors scored a mean above 3 - 'helpful'. Conclusion: No individual story or metaphor stood out as being predominately important in being helpful in the recovery process through the use of PNE. Clinical implications: The overall messages of reconceptualising pain during PNE may be more important than any individual story or metaphor.